(1547) Economic Efficiency and Resource Productivity on Small Broiller Farms in Saudi Arabi الكفاءة الاقتصادية وإنتاجية الموارد في مزارع الدجاج اللاحم الصغيرة في المملكة العربية السعودية - Risk, Mohamed M. (The Institute of National Planning, 2018)

(untitled)
Increasing attention has been focused upon resource Productivity and adjustment problems of agriculture during recent years in the kingdom of Saudi Arabia; more foods have to be produced each year to satisfy the increasing needs of Thermopylaetion and to provide sufficient row material for industrial development.